A Phylogenetic Re-Evaluation of the Stenakrine Opecoelids (Trematoda, Digenea: Opecoeloidea) with Some Taxonomic Novelties - Sergey G. Sokolov; Sergei V. Shchenkov; Eugeniy V. Frolov; Ilya I. Gordeev (Diversity, 2022)
The Opecoeloidea is a large group of xiphidiate digeneans parasitizing marine and freshwater fishes. According to the current taxonomic model, this superfamily contains only one family with numerous subfamilies. This study is devoted to the members of the Stenakrinae. Based on phylogenetic analysis of concatenated sequences of 18S and 28S rRNA genes of stenakrine opecoelids Caudotestis dobrovolski, C. cf. dobrovolski, Hexagrammia zhukovi, Stenakron vetustum, as well as the deep-sea xiphidiate digenean Zdzitowieckitrema incognitum, which so far has had an ambiguous phylogenetic status, we erect a new opecoeloid family, the Zdzitowieckitrematidae fam. nov. The genera Holsworthotrema and Scorpidotrema are removed from the Stenakrinae to the Scorpidotrematinae subfam. nov. within the Opecoelidae. We also remove the Stenakrinae from the Opecoelidae and recognize it as a separate family within the Opecoeloidea. The Stenakridae stat. nov. is a sister taxon to a well-supported Opecoelidae. The Zdzitowieckitrematidae occupies a sister position relative to the stenakrids and the opecoelids taken together. All three families are clearly phylogenetically distinct, however convincing morphological differences are revealed only between the Zdzitowieckitrematidae and the Stenakridae and between the Opecoelidae and the Stenakridae.